Congenital Heart Surgery Nomenclature and Database Project: patent ductus arteriosus, coarctation of the aorta, interrupted aortic arch - Backer, Carl L; Mavroudis, Constantine (The Annals of thoracic surgery, 2000)
The extant nomenclature for patent ductus arteriosus (PDA), coarctation of the aorta (CoAo), and interrupted aortic arch (IAA) is reviewed for the purpose of establishing a unified reporting system. The subject was debated and reviewed by members of the STS-Congenital Heart Surgery Database Committee and representatives from the European Association for Cardiothoracic Surgery. All efforts were made to include all relevant nomenclature categories using synonyms where appropriate. PDA is subclassified by origin, insertion, and patient weight. CoAo is subclassified into isolated CoAo, CoAo with ventricular septal defect, and CoAo with complex intracardiac anomalies. IAA is subclassified into anatomic types A, B, and C based on the location of the interruption. A comprehensive database set is presented which is based on a hierarchical scheme. Data are entered at various levels of complexity and detail which can be determined by the clinician. These data can lay the foundation for comprehensive risk stratification analyses. A minimum database set is also presented which will allow for data sharing and would lend itself to basic interpretation of trends. Outcome tables relating diagnoses, procedures, and various risk factors are presented.